Critical Synthesis Package: Learning Style Type Indicator - Wanda Reygaert (Association of American Medical Colleges, 2014)
Abstract This Critical Synthesis Package contains: (1) a Critical Analysis of the psychometric properties and the application to health science education of the Learning Style Type Indicator (LSTI), and (2) a copy of the LSTI instrument developed by John Pelley, PhD. The LSTI is a self-administered instrument containing 28 questions. For each question respondents must select one of two possible letter options. There are four different letter choice pairings, with certain items having different letter pairs to choose from. The responses are summarized to determine which letters from each answer pair occurs most as an answer choice. The resulting four letters are arranged to determine the respondent's learning type. The LSTI is based on proven psychological theory, including the Myer-Briggs Type Indicator (MBTI). The author has used the LSTI at his home academic institution as a self-help tool for medical students. The LSTI has been compared to other similar instruments in two validity studies. These studies found the LSTI to have partial validity (one dimension out of four). More studies need to be conducted to assess the validity of the LSTI directly. The LSTI seems to be based on sound, proven psychological theory, and may need some minor revision to make it a very useful instrument.